Criminal Sanctions Against Perpetrators of the Commercial Sexual Exploitation of Children: A Comparative Study of Indonesian Positive Law and Islamic Criminal Law - Rusydi Mulya Sumantri; Sukiati (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2025)
The Commercial Sexual Exploitation of Children (CSEC) constitutes a serious violation of human rights and human dignity. In Medan City, CSEC practices occur in an organized and recurring manner, underscoring the need to evaluate the effectiveness of existing criminal sanctions. This study aims to compare criminal sanctions for CSEC offenders under Indonesian positive law and Islamic criminal law and to formulate normative contributions for strengthening child protection. Using a normative juridical and comparative legal approach, this research examines sanction provisions in the Indonesian Criminal Code (KUHP), Law No. 35 of 2014 on Child Protection, and Law No. 21 of 2007 on Human Trafficking, as well as the concepts of hudud and ta?z?r in Islamic criminal jurisprudence (fiqh jinayah). The findings reveal fundamental differences between the two systems: Indonesian positive law emphasizes legal certainty and rehabilitation through imprisonment and fines, while Islamic criminal law prioritizes moral deterrence through hudud and the flexibility of ta?z?r. This article contributes by proposing harmonization between the two systems through offense reformulation, strengthened sanctions, and the implementation of preventive policies grounded in religious values to enhance child protection against systemic sexual crimes.